Applications of blockchain in business processes: a comprehensive review - Viriyasitavat, Wattana (2023)
Blockchain (BC), as an emerging technology, is revolutionizing Business Process Management (BPM) in multiple ways. The main adoption is to serve as a trusted infrastructure to guarantee the trust of collaborations among multiple partners in trustless environments. Especially, BC enables trust of information by using Distributed Ledger Technology (DLT). With the power of smart contracts, BC enforces the obligations of counterparties that transact in a business process (BP) by programming the contracts as transactions. This paper aims to study the state-of-the-art of BC technologies by (1) exploring its applications in BPM with the focus on how BC provides the trust of BPs in their lifecycles; (2) identifying the relations of BPM as the need and BC as the solution with the assessment towards BPM characteristics; (3) discussing the up-to-date progresses of critical BC in BPM; (4) identifying the challenges and research directions for future advancement in the domain. The main conclusions of our comprehensive review are (1) the study of adopting BC in BPM has attracted a great deal of attention that has been evidenced by a rapidly growing number of relevant articles. (2) The paradigms of BPM over Internet of Things (IoT) have been shifted from persistent to transient, from static to dynamic, and from centralized to decentralized, and new enabling technologies are highly demanded to fulfill some emerging functional requirements (FRs) at the stages of design, configuration, diagnosis, and evaluation of BPs in their lifecycles. (3) BC has been intensively studied and proven as a promising solution to assure the trustiness for both of business processes and their executions in decentralized BPM. (4) Most of the reported BC applications are at their primary stages, future research efforts are needed to meet the technical challenges involved in interoperation, determination of trusted entities, confirmation of time-sensitive execution, and support of irreversibility.